A mutual-aid mechanism for supply chains with capital constraints. Issue 4 (2nd October 2019) - Peng, Hongjun; Pang, Tao
ABSTRACT: We consider a supply chain in which both the supplier and the distributor experience capital constraints. Due to the capital constraints, the supplier faces a capital deficit during the production period and the distributor faces a capital deficit during the sales period. Under the bank loan financing, we derive the optimal strategies for both the supplier and the distributor. Then we propose a mutual-aid mechanism under which the distributor provides an advance payment to the supplier during the production period, and the supplier offers a deferred payment trade credit to the distributor during the sales period. As the demand is uncertain, there is a bankruptcy risk with the distributor, which is taken into consideration in our model. We develop a Stackelberg game model and derive the optimal strategies under the mutual-aid mechanism. Our results indicate that the mutual-aid mechanism can improve the profits for both the supplier and the distributor, comparing to the bank loan financing case.